Flexible constantan film thermoelectric device with high power density and preparation method and application thereof

Through the series connection and tin-lead welding technology of Conco copper film outriggers composed of Cu55Ni42Mn3 and combined with the rolling process, the problems of performance attenuation and high contact resistance of flexible thermoelectric materials after bending are solved, high power density and excellent flexibility are achieved, and significantly improved Performance of flexible thermoelectric devices.

CN119300693APending Publication Date: 2025-01-10TONGJI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411305089.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The thermoelectric properties of existing flexible thermoelectric materials and devices are significantly attenuated after flexible deformation, and the traditional connection method leads to high contact resistance, limiting high power output.

Method used

The n-type Conco copper film outrigger consisting of Cu55Ni42Mn3 is connected in series through copper wire, and soldered with tin lead solder to form a linear or annular tandem structure. The film with high elastic modulus and high dislocation density is obtained by combining the rolling process to reduce interface contact. resistance.

Benefits of technology

High power density and excellent flexibility are achieved. The performance of Kangco Copper thin-film thermoelectric devices is basically maintained after 1000,000 bending times, the interface contact resistivity is significantly lower than that of the existing technology, and the power density reaches 301.78W·m-2, showing the flexibility of inorganic materials. Great potential in thermoelectric devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a flexible constantan thin film thermoelectric device with high power density and a preparation method and application thereof, the flexible constantan thin film device is formed by connecting a plurality of n-type constantan thin film supporting legs in series through copper wires, and the n-type constantan thin film supporting legs are composed of Cu55Ni42Mn3. Compared with the prior art, the preparation of the flexible thermoelectric thin film device utilizes the constantan metal bond connection characteristic, the constantan thin film material with the micron-order thickness is obtained through the rolling technology, the texture orientation with the optimal elastic modulus and the high dislocation density are achieved, the flexible thermoelectric thin film device has the excellent flexibility and elasticity, the preparation technology is simple, and the preparation cost is low. The assembled 10-leg flexible thermoelectric thin film device is far superior to a currently reported flexible thermoelectric device in the aspects of power density and bending flexibility. The metal film thermoelectric device overcomes the inherent rigidity of an inorganic thermoelectric material, has the characteristic of high power factor of constantan, and shows that the metal material has potential in the aspect of application of the flexible thermoelectric device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermoelectric materials and devices, and in particular to a flexible constantan thin film thermoelectric device with high power density, and a preparation method and application thereof. Background Art

[0002] With the rapid development of Internet of Things technology, flexible electronic products are rapidly becoming popular. In order to improve the convenience and durability of flexible electronic products, it is necessary to develop self-powered, easy-to-carry, highly reliable, and ultra-thin flexible power sources. Flexible thermoelectric materials can achieve direct conversion of thermal energy and electrical energy through the Seebeck effect, providing a solution for sustainable power supply of wearable devices. The performance of thermoelectric materials is measured by the dimensionless figure of merit zT, zT = S 2 T / ρκ, where S is the Seebeck coefficient, ρ is the resistivity, κ is the thermal conductivity, and T is the absolute temperature. 2 σ is called the power factor (PF). Given a given temperature difference, the output power of a flexible thermoelectric device is directly related to the material's power factor, so the power factor is used to evaluate the thermoelectric performance of the film.

[0003] Traditional thermoelectric materials, due to their covalent or ionic bonded properties, exhibit inherent rigidity, making them unable to withstand flexible deformation. Conductive polymers such as PPy, PANI, and PEDOT:PSS are used in flexible thermoelectric devices due to their good flexibility and inherent low thermal conductivity, but the low thermoelectric performance caused by the low carrier mobility and low electrical conductivity of polymers limits their further application.

[0004] Combining the good flexibility and low thermal conductivity of conductive polymers with the good electrical transport properties of inorganic materials is another strategy to improve thermoelectric performance, but the production process is complicated and the efficiency is relatively low. In addition, considering the inherent outstanding properties of all inorganic thermoelectric materials, forming inorganic films on flexible substrates such as nylon and polyimide (PI) is also a strategy aimed at improving flexibility without sacrificing high thermoelectric performance. This strategy is limited by the thermal stability of the substrate and the risk of separation during use, but the thermoelectric performance decays significantly after multiple bending.

[0005] At present, the research on flexible thermoelectric technology mainly focuses on organic thermoelectric materials, organic-inorganic composite thermoelectric materials and all-inorganic flexible thermoelectric materials. Although organic thermoelectric materials have good flexibility and plasticity, their electrical properties are poor, resulting in output voltage and power far lower than inorganic materials. The structure and process of organic-inorganic composite thermoelectric materials are complex, making it difficult to prepare ultra-thin flexible devices, and their performance degrades significantly under bending and cyclic service conditions. The inherent deformability of inorganic semiconductor films can be significantly enhanced, but existing research on thermoelectric films generally shows that compared with bulk materials, thermoelectric films not only have significantly poorer output power, but also have the problem of cyclic performance degradation. Summary of the invention

[0006] The purpose of the present invention is to overcome the above problems existing in the prior art and to provide a flexible constantan thin film thermoelectric device with high power density and a preparation method and application thereof.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] One of the technical solutions of the present invention is to provide a flexible constantan thin film thermoelectric device with high power density, which is composed of a plurality of n-type constantan thin film legs connected in series, wherein the chemical composition of the n-type constantan thin film legs is Cu 55 Ni 42 Mn3.

[0009] In some specific implementation methods, a plurality of the n-type constantan thin film legs are connected in series via copper wires, and the electrodes connecting the n-type constantan thin film legs and the copper wires are tin-lead solder joints.

[0010] In some specific implementation methods, the series connection structure is a linear series connection or a ring series connection.

[0011] In some specific implementations, the n-type constantan thin film has 10 legs.

[0012] In some specific implementation methods, the n-type constantan thin film leg has a length of (27-33) mm, a width of (2-8) mm, and a thickness of less than 50 μm.

[0013] As a more preferred embodiment, the n-type constantan thin film leg has a length of 30 mm, a width of 5 mm, and a thickness of 25 μm.

[0014] The present invention uses tin-lead solder for welding and copper wire for connection and assembly. Due to the excellent weldability of constantan, the contact resistance is effectively reduced, which is an important factor in achieving high power output.

[0015] A second technical solution of the present invention is to provide a method for preparing a flexible constantan thin film thermoelectric device as described in one of the above solutions, comprising the following steps:

[0016] S1. Change the chemical composition to Cu 55 Ni 42 The Mn3 Constantan foil is cut into n-type Constantan thermoelectric thin film legs of target size;

[0017] S2. Apply phosphoric acid to both ends of the legs of the n-type constantan thermoelectric film, solder the copper wire to the location where the phosphoric acid is applied on the legs of the n-type constantan thermoelectric film with solder, and connect several legs of the n-type constantan thermoelectric film in series in the same manner to obtain a flexible constantan thin film thermoelectric device.

[0018] In some specific embodiments, in step S1, the chemical composition is Cu 55 Ni 42 The preparation process of copper foil with chemical composition of Cu 55 Ni 42 The Mn3 Constantan strip is subjected to a multi-pass rolling process to obtain a Constantan foil with a thickness of less than 50 μm.

[0019] In some specific embodiments, the rolling process is a cold rolling process.

[0020] A third technical solution of the present invention is to provide an application of a flexible constantan thin film thermoelectric device with high power density as described in one of the above technical solutions, wherein the flexible constantan thin film thermoelectric device is used to prepare wearable devices.

[0021] Constantan is a classic Cu-Ni based alloy with excellent electrical conductivity (about 10 6 S m -1 ) and almost the highest absolute Seebeck coefficient among alloys (about 40μV / K at room temperature), so it has a high power factor. In addition, the metallic bond structure of constantan gives it high ductility and plasticity, allowing it to be processed into thin films through deformation processing such as rolling. These characteristics make constantan films have both the high power factor and excellent mechanical properties of inorganic materials, showing potential for application in wearable electronic devices. On the other hand, as a metal material, constantan exhibits excellent welding properties. The contact resistivity can be effectively reduced by using tin-lead solder and copper wire to assemble the constantan legs in series. Among them, the interface resistivity of the thermoelectric film legs is about 0.03mΩ·cm 2 , which is significantly lower than the contact resistivity of flexible thin film thermoelectric devices reported in the literature, so this method can achieve higher device output power. The above excellent film material properties and electrode structure enable a 10-legged constantan flexible thin film device to achieve about 301.78W·m at a temperature difference of 101K. -2 The power density is the highest among the thin-film thermoelectric devices reported so far. At the same time, the high elastic modulus orientation and high dislocation concentration brought about by rolling give the film excellent resilience. After testing, the constantan film can be bent 1,000,000 times around the dimension of an adult's little finger (bending radius 5 mm) while the performance remains basically unchanged. Both in terms of mechanical flexibility and power output, the constantan film and its thermoelectric device of the present invention have achieved significant breakthroughs, demonstrating the great potential of inorganic materials in the application field of flexible thermoelectric devices, and are expected to be used in wearable devices in the future.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) Currently, the research on flexible thermoelectric technology mainly focuses on organic thermoelectric materials, organic-inorganic composite thermoelectric materials and all-inorganic flexible thermoelectric materials. Although organic thermoelectric materials have good flexibility and plasticity, their electrical properties are relatively poor, resulting in output voltage and power far lower than those of inorganic materials. The structure and process of organic-inorganic composite thermoelectric materials are complex, making it difficult to prepare ultra-thin flexible devices, and their performance degrades significantly under bending and cyclic service conditions. The inherent deformability of inorganic semiconductor films can be significantly enhanced, but existing thermoelectric film research generally shows that compared with bulk materials, thermoelectric films not only have significantly poorer output power, but also have the problem of cyclic performance degradation. The high power factor (S 2 σ~40μW·cm - 1 K -2 ) is used to prepare thin-film thermoelectric materials from constantan, and the plasticity of the metal is used to roll constantan into <111> The film with cross-sectional texture orientation, i.e., optimal elastic modulus orientation, further increases the dislocation density and elasticity through the plastic deformation process of material thinning, so that the film exhibits excellent resilient flexibility, and its performance remains basically unchanged after bending 1,000,000 times under the condition of a curvature radius of 5 mm. Therefore, the constantan film prepared by the present invention has both excellent flexibility and thermoelectric properties.

[0024] (2) At present, the connection between electrodes and materials in flexible devices usually adopts cumbersome evaporation technology or silver paste with poor wettability. However, the material / electrode interface formed by these two methods often has a high contact resistance. The present invention utilizes the excellent solderability of constantan and uses tin-lead solder and copper wire to assemble the constantan legs in series, which can effectively reduce the contact resistivity. In addition, this method is easy to operate. Therefore, the constantan thin film thermoelectric device prepared by the present invention achieves low interface contact resistivity to obtain high power density, and this connection method has strong universality for metal thermoelectric materials. The constantan thin film thermoelectric device prepared by the present invention not only retains excellent thermoelectric properties, but also overcomes the inherent rigidity of inorganic thermoelectric materials. The specifically oriented texture and high dislocation density make it have excellent flexibility, showing the great potential of constantan in the application of flexible thermoelectric devices.

[0025] (3) The preparation of the flexible thermoelectric thin film device of the present invention utilizes the characteristics of constantan metal bond connection. The constantan thin film material with micron-level thickness is obtained through a rolling process, and has a texture orientation with an optimal elastic modulus and a high dislocation density, so that it has excellent flexibility and elasticity. The preparation process is simple, and the assembled 10-leg flexible thermoelectric thin film device is far superior to the currently reported flexible thermoelectric devices in terms of power density and bending flexibility. The metal thin film thermoelectric device overcomes the inherent rigidity of inorganic thermoelectric materials and has the characteristics of constantan's own high power factor, showing the potential of metal materials in the application of flexible thermoelectric devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Cu is obtained by DFT and flexibility matrix calculation 50 Ni 50 Full-space mapping of the elastic modulus (a) and the corresponding 2D contours on the equivalent {100}, {010}, and {001} planes (b).

[0027] Figure 2 XRD diffraction spectra of the cross section and surface of a 25 μm thick constantan film (a) and the surface of constantan films of different thicknesses during rolling (b).

[0028] Figure 3 SEM images of the cross section of constantan thermoelectric films of different thicknesses.

[0029] Figure 4 The anti-pole figure distribution diagram (magnified dislocation) and the corresponding pole figure and anti-pole figure of the cross-section (a) and surface (b) of the rolled 25 μm thick constantan film.

[0030] Figure 5 This is the TEM image of the 25 μm thick constantan film obtained by rolling.

[0031] Figure 6 The stress-strain curves of the 25 μm thick constantan film obtained by rolling before and after rolling annealing.

[0032] Figure 7 The relationship between the Seebeck coefficient (S), resistivity (ρ), power factor (PF) and temperature of constantan thermoelectric films with different rolling thicknesses.

[0033] Figure 8 Interfacial contact resistivity of the thermoelectric film legs and comparison with values ​​reported in the literature.

[0034] Fig. 9 The relationship between the load voltage (V), output power (P) and loop current (I) of the thermoelectric thin film device under different temperature differences, the maximum power density (P d max ) changes with temperature difference and comparison of normalized output power density of devices.

[0035] Fig.10 is the open circuit voltage (V oc )(a) Internal resistance (R in )(b) and maximum output power density (P max )(c) Relationship with temperature difference.

[0036] Fig.11The resistance change of the constantan film when the bending radius is 5 mm (R / R initial ), Seebeck coefficient change (S / S initial ), power factor change (PF / PF initial ) and resistance change (R / R initial ) and the B factor. DETAILED DESCRIPTION

[0037] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0038] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.

[0039] Embodiment 1:

[0040] This embodiment provides a method for preparing a flexible constantan thin film thermoelectric device, comprising the following steps:

[0041] (1) Using 1.5mm thick Cu 55 Ni 42 Mn3 Constantan strip is used as the starting material, and a multi-pass cold rolling process is used to reduce the thickness of Constantan foil to 25μm.

[0042] (2) The obtained Constantan copper foil is cut into Constantan copper thermoelectric film legs with a length of 30 mm and a width of 5 mm.

[0043] (3) Use a cotton swab to apply phosphoric acid on both ends of the legs of the constantan thermoelectric film, use solder to solder the copper wire to the location where the phosphoric acid is applied on the legs of the constantan thermoelectric film, and connect several legs of the constantan thermoelectric film in linear series in the same way to obtain a flexible constantan thin film device.

[0044] The prepared flexible constantan thermoelectric thin film device was subjected to performance testing, and the results are as follows:

[0045] Considering Cu 55 Ni 42 Mn3 has a low Mn content, so the actual composition is approximated to Cu 50 Ni 50 Perform DFT calculations, Figure 1 The Cu calculated by DFT and flexibility matrix is ​​shown. 50 Ni 50The full-space mapping of the elastic modulus (a) and the corresponding 2D contours on the equivalent {100}, {010}, and {001} planes (b) show that the CuNi <111> and <100> The modulus ratio is as high as 2.3. <111> The elastic modulus is maximum in this direction.

[0046] Figure 2 The cross section and surface of a 25 μm thick Constantan film (a), the XRD diffraction patterns of the surfaces of Constantan films of different thicknesses during rolling (b), and the plane and cross section XRD patterns of a 25 μm thick Constantan film ( Figure 2 a) shows that the 25 μm thick rolled film has obtained an ideal rolling orientation, and the cross section is (111) oriented. XRD patterns of films with different thicknesses during rolling ( Figure 2 b) It can be seen that the film orientation changes during the rolling process, and the film becomes in the ideal rolling orientation below 50μm.

[0047] Figure 3 The SEM images of the cross-section of the Constantan thin film with different thicknesses show that the thickness of the Constantan thermoelectric thin film is relatively uniform.

[0048] Figure 4 The cross-section (a) and surface (b) of a 25 μm thick constantan film obtained by rolling (magnified dislocation) and the corresponding pole figure and anti-pole figure. Multiple cold rolling can form a film with a density of 10 14 m -2 The dislocation of the sample, the EBSD orientation results correspond to the XRD results, the cross section is (111) orientation, and the surface is (110) orientation.

[0049] Figure 5 TEM image of a 25 μm thick Constantan film obtained by rolling. The TEM image shows dense dislocations (a) and details of the Burgers vector (b) as well as the corresponding strain distribution.

[0050] Figure 6 The stress-strain curves of the 25 μm thick constantan film obtained by rolling before and after rolling annealing are shown. Before annealing, the film has a high elastic modulus orientation. The maximum elastic strain of the cold-rolled foil with a (111) cross-sectional orientation and dense dislocations is greatly enhanced.

[0051] Figure 7 The temperature-dependent performance curves of constantan thermoelectric films with different rolling thicknesses are shown in Figure 2. Figure 7 a is the relationship between resistivity ρ and temperature, Figure 7 b is the relationship between Seebeck coefficient (S) and temperature, Figure 7 c is the relationship between power factor (PF) and temperature. It shows that the thermoelectric properties of the constantan thin film materials with different thicknesses obtained by the preparation method are basically the same, and the power factor PF ( Figure 7 c) Comparable to inorganic non-metallic thermoelectric materials in the range of 150K above room temperature.

[0052] like Figure 8 As shown in the figure, the interface contact resistivity of the thermoelectric film legs is about 0.03 mΩ·cm using the four-probe method. 2 The comparison of the contact resistance of the thermoelectric legs of typical thermoelectric thin film elements in the literature shows that the use of tin-lead solder to solder the series copper wires to make electrodes has the lowest interface resistivity, which can reduce the adverse effect of interface resistance on the output power of the device.

[0053] Fig. 9 The figure is the performance test result of 10-leg constantan thin film thermoelectric device, which reflects the relationship between the load voltage (V), output power (P) and loop current (I) of the thermoelectric thin film device under different temperature differences (a). Fig. 9 aWith the increase of loop current, the load voltage gradually decreases. This is mainly because when the temperature difference is constant, the increase of loop current is due to the reduction of the resistance of the load resistor, so the load voltage decreases. At the same time, the voltage value will increase with the increase of temperature difference. Unlike the load voltage, the output power will reach a peak value as the loop current increases, and then decrease. This peak value generally occurs when the load resistance is equal to the internal resistance of the module. At the same time, the greater the temperature difference, the greater the output power. Maximum power density (P d max ) changes with temperature difference and the comparison of the normalized output power density of the device is shown in the figure Fig. 9 As shown in Fig. 9c, when the temperature difference is 101.9K, the maximum output power density of the thin film thermoelectric device is about 301.78W·m -2 , which is much higher than most reported thin-film thermoelectric devices. The device’s normalized output power density is about 7.27 μW cm -1 K -2 , which is much higher than most reported thin film thermoelectric devices.

[0054] Fig.10 The open circuit voltage (V oc )( Fig.10 a) Internal resistance (R in )( Fig.10 b) and maximum output power density (P max )( Fig.10 c) Relationship with temperature difference: The open circuit voltage is comparable to the voltage value calculated by the Seebeck coefficient of the material and the temperature difference, indicating that the structure of the constantan thin film thermoelectric device of the present invention involves less heat loss.

[0055] Fig.11 The resistance (R / R) of the constantan film after bending 1,000,000 times at a bending radius of 5 mm is shown.initial )( Figure 8 a) and Seebeck coefficient (S / S initial )( Figure 8 b) and power factor (PF / PF initial )( Figure 8 c) No significant changes, and Fig.11 d shows the resistance change (ΔR / R) of the constantan film after bending 1,000,000 times at a bending radius of 5 mm. initial ) and B factor (B = bending times / bending radius), and compared with flexible thermoelectric films in the literature, it shows excellent flexibility.

[0056] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A flexible constantan thin film thermoelectric device with high power density, characterized in that: It is composed of several n-type constantan thin film legs connected in series, and the chemical composition of the n-type constantan thin film legs is Cu 55 Ni 42 Mn3.

2. The flexible constantan thin film thermoelectric device with high power density according to claim 1, characterized in that: A plurality of the n-type constantan thin film legs are connected in series via copper wires, and the electrodes connecting the n-type constantan thin film legs and the copper wires are tin-lead solder joints.

3. The flexible constantan thin film thermoelectric device with high power density according to claim 1, characterized in that: The series connection structure is a linear series connection or a ring series connection.

4. The flexible constantan thin film thermoelectric device with high power density according to claim 1, characterized in that: The n-type constantan thin film has 10 legs.

5. The flexible constantan thin film thermoelectric device with high power density according to claim 1, characterized in that: The n-type constantan thin film legs have a length of (27-33) mm, a width of (2-8) mm, and a thickness of less than 50 μm.

6. The flexible constantan thin film thermoelectric device with high power density according to claim 5, characterized in that: The n-type constantan thin film legs have a length of 30 mm, a width of 5 mm, and a thickness of 25 μm.

7. A method for preparing a flexible constantan thin film thermoelectric device with high power density as claimed in any one of claims 1 to 6, characterized in that: The steps include: S1. Change the chemical composition to Cu 55 Ni 42 The Mn3 Constantan foil is cut into n-type Constantan thermoelectric thin film legs of target size; S2. Apply phosphoric acid to both ends of the legs of the n-type constantan thermoelectric film, solder the copper wire to the location where the phosphoric acid is applied on the legs of the n-type constantan thermoelectric film with solder, and connect several legs of the n-type constantan thermoelectric film in series in the same manner to obtain a flexible constantan thin film thermoelectric device.

8. The preparation method according to claim 7, characterized in that: In step S1, the chemical composition is Cu 55 Ni 42 The preparation process of copper foil with chemical composition of Cu 55 Ni 42 The Mn3 Constantan strip is subjected to a multi-pass rolling process to obtain a Constantan foil with a thickness of less than 50 μm.

9. The preparation method according to claim 8, characterized in that: The rolling process is a cold rolling process.

10. An application of a flexible constantan thin film thermoelectric device with high power density as claimed in any one of claims 1 to 6, characterized in that: The flexible constantan thin film thermoelectric device is used for preparing wearable devices.